Improving Studentsâ€Ÿ Listening Competence by Using Contextual Teaching and Learning (A Classroom Action Research Conducted at the Second Grade of MTs. Maâ€Ÿarif 2 Muntilan, Magelang) - Annisa, Happy; viani, Octa; Hermayawati, Hermayawati (LPPM Universitas Mercu Buana Yogyakarta, 2015)
his research was conducted to improve studentsâ€Ÿ listening competence byusing Contextual Teaching and Learning (CTL) method. The aims of conducting thisresearch were as follows: (1) improving studentsâ€Ÿ listening competence through CTL;(2) finding the studentsâ€Ÿ interest improvement on their listening by using CTL; (3)finding the improvement of the studentsâ€Ÿ listening competence by using CTL. TheClassroom Action Research was used by the researcher in conducting this research.Furthermore, the pre-test, treatments, and post-test were given to find the studentsâ€Ÿlistening improvement in learning using CTL.The result of the research showed thatCTL could improve the studentsâ€Ÿ listening competence. It could be seen from theaverage scores in the pre-test and post-test. The average score of students in the pretestwas about fifty six point two. Meanwhile, the average score in the first post-test andsecond post-test were seventy two point five and eighty point six. The result of thestudentsâ€Ÿ average score showed the improvement in their listening achievement by byusing CTL. The studentsâ€Ÿ interest improved through the studentsâ€Ÿ active contributionduring the learning processes which was measured by using scoring rubric ofâ€œmetacognitive rubric motivationâ€. Therefore, it can be concluded that CTL is effectiveto teach listening to the students. In short, the method can be used by the teacher as analternative to teach listening.Keywords: Classroom Action Research, CTL, Listening, Method, Motivation